Online marketplace analysis - Chaffey, Dave (Henry Stewart Talks, 2010)
Micro and macro-factors, Reasons for analysis, Online SWOT analysis, Key marketplace actors, Customer behavior models, Search keyphrase behavior, Online value proposition, Competitor analysis, Intermediary analysis, Introduction to 6 digital communications, Digital channel governance